Towards which Representation? (diségno, 2018)
It was important for the first Focus of the 2017 UIDConvention in Naples to be centered on the theme ofthe identity of drawing in terms of temporal evolution.It is the first reflection that we participants are calledto face and that we “must” know how to deal with. Thefirst question we ask ourselves, coherently with what isrequested of us, is, in fact, how we stand today in thecontext of an evolution that has important repercussionseven on teaching –if there has actually been an evolution–and how we relate to its undeniable metamorphosesor, more properly, “mutations” as Darwin would callthem.